2006
DOI: 10.1099/jmm.0.46845-0
|View full text |Cite
|
Sign up to set email alerts
|

Protease IV production in Pseudomonas aeruginosa from the lungs of adults with cystic fibrosis

Abstract: Protease IV is important in the pathogenesis of Pseudomonas aeruginosa-induced microbial keratitis, but little is known of its role in cystic fibrosis (CF) lung infection. In this study protease IV production was examined in 43 P. aeruginosa isolates (24 non-clonal and 19 clonal) from the lungs of chronically infected adult patients attending the Royal Prince Alfred Hospital CF Clinic, Sydney, Australia. Overall, 32/43 (74 %) isolates were positive for protease IV protein by Western blotting and 22/43 (51 %) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…These results are consistent with those of our previous study of protease IV activity using the same isolates (40). The focus on proteases reflects previous reports that both the United Kingdom CF LES (34) and an epidemic ocular P. aeruginosa strain had increased protease activity (26).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with those of our previous study of protease IV activity using the same isolates (40). The focus on proteases reflects previous reports that both the United Kingdom CF LES (34) and an epidemic ocular P. aeruginosa strain had increased protease activity (26).…”
Section: Discussionsupporting
confidence: 83%
“…The CF Liverpool epidemic strain (LES) has shown high levels of expression of virulence factors, including elastase and staphylolysin, associated with the premature activation of QS systems (34), and a virulent epidemic clone isolated from patients with microbial keratitis has been characterized by high activities of an elastase variant (26). Our previous study of AES-1, AES-2, and nonclonal P. aeruginosa isolates from subjects with CF showed that clonal isolates were more likely to have protease IV activity than nonclonal isolates (40). Enhanced protease IV activity may promote tissue destruction and inflammation and facilitate host-to-host spread.…”
mentioning
confidence: 99%
“…The metalloproteases Pseudomonas elastase B, alkaline protease (AprA), and protease LasA (staphylolysin) are released by P. aeruginosa (41). P. aeruginosa also produces serine protease IV, which can degrade surfactant (1).…”
Section: Discussionmentioning
confidence: 99%
“…protease, and hemolytic phospholipase (2)(3)(4)(5)(6). Secreted toxins and enzymes frequently assemble in the periplasm as proenzymes and are exported to the growth media as inactive proteins.…”
mentioning
confidence: 99%